Reclaiming the Street in Toni Morrison's Jazz. (19th January 2022) - Smith, Alexandra
Abstract: The call and response protest chants of "Whose streets? Our streets!" that echo throughout city streets in the midst of Black Lives Matter protests and marches illustrate one of many ways in which US streets have been reclaimed and repurposed, particularly against police violence against brown and Black bodies. The street's capacity to function as a site of converging, colliding, and contradicting perspectives and ideologies also functions as a rich, nuanced lens for reading literature. Proceeding from Michel Foucault's theoretical framework that space is "fundamental to any exercise of power, " I read the representation of early twentieth-century Harlem and its network of streets in Toni Morrison's Jazz (1992) as sites of "contradictory possibilities." In Jazz, I argue, the street becomes a character unto itself: an artery that facilitates a sense of community, belonging, and play while simultaneously revealing tensions and temptations and harboring violence. These streets are also Black spaces, in stark contrast to the "dollar-wrapped fingers" of whiteness that poke and prod south of 110th street. As such, whiteness is physically decentered, allowing for the complexity of Black life to be explored in its movements in, through, and around the city streets. Building on Edward Soja's theory of "third space"—a combination of material and imaginative worlds—I argue that the novel opens up new possibilities for reclaiming the material street as a site where institutionalized violence and the systemic racism that feeds it can be subversively resisted.